Marilena Koppa. The Evolution of the Common Security and Defence Policy: Critical Junctures and the Quest for EU Strategic Autonomy - Pilitauskas, Ovidijus (Politologija, 2024)
Marilena Koppa. The Evolution of the Common Security and Defence Policy: Critical Junctures and the Quest for EU Strategic Autonomy. St Antony’s Series. Cham: Springer International Publishing, 2022 // https://doi.org/10.1007/978-3-030-99158-6.